THE INFLUENCE OF MEETING ON GOODS AND SERVICE BRAND IMAGE IN FORMING LOYALTY - Hansen Prasetio; Sarwo Edy Handoyo (Graduate Program of Universitas Tarumanagara, 2025)
This research aims to determine the effect of goods brand image and service brand image on brand loyalty, with the willingness to make appointments as a mediating variable. The sampling technique used in this research is non-probability sampling with a purposive sampling approach. The respondents in this research consisted of 92 employees working as procurement/purchasing, engineers/technicians, or estimators/quantity surveyors in private companies engaged in development, contracting, or system integration located in Jabodetabek. The data analysis technique used in this research is qualitative data analysis using SmartPLS version 4.1.1.3. The results show that both goods brand image and service brand image have a positive but not significant effect on brand loyalty. Goods brand image has a positive but not significant effect on the willingness to make appointments. Service brand image has a positive and significant effect on the willingness to make appointments. The willingness to make appointments has a positive and significant effect on brand loyalty. The willingness to make appointments can mediate the effect of service brand image on brand loyalty, whereas it cannot mediate the effect of goods brand image on brand loyalty.